Challenges and Opportunities of Nuclear Medicine in Health Care - Gupta, Arun K. (Asian Journal of Pharmaceutical and Clinical Research, 2019)
AERB Sponsored National Seminar Challenges and Opportunities of Nuclear Medicine in Health Care (Saturday 02 February 201 Organized by-Chameli Devi Institute of Pharmacy, Indore